2021
DOI: 10.15835/nbha49312489
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of Hydroxycinnamoyl CoA: Shikimate Hydroxycinnamoyl Transferase (HCT) gene family in Carthamus tinctorius L.

Abstract: Hydroxycinnamoyl-CoA: shikimate hydroxycinnamoyl transferase (HCT) is mainly associated with monolignol biosynthesis, a central precursor to producing guaiacyl and syringyl lignins in plants. However, the explicit regulatory mechanism of HCT-mediated monolignol biosynthesis in plants still remained unclear. Here, the genome-wide analysis of the HCT gene family in Carthamus tinctorius as a target for understanding growth, development, and stress-responsive mechanisms was investigated. A total of 82 CtHCT genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For instance, transcriptomic analysis revealed that the HCT genes were significantly up-regulated in C. tinctorius inflorescences treated with MeJA, indicating their potential involvement in the process of MeJA-induced flavonoid accumulation in the inflorescences [ 11 ]. Furthermore, a series of HCT genes were identified in the C. tinctorius genome using the Hidden Markov Model, and their expression patterns were analyzed in MeJA-treated flowers at different developmental stages, revealing structural and expression differences among them [ 34 ]. However, the aforementioned studies were limited to transcriptomic or bioinformatic analyses and did not further validate the functions of the identified HCT genes in C. tinctorius .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, transcriptomic analysis revealed that the HCT genes were significantly up-regulated in C. tinctorius inflorescences treated with MeJA, indicating their potential involvement in the process of MeJA-induced flavonoid accumulation in the inflorescences [ 11 ]. Furthermore, a series of HCT genes were identified in the C. tinctorius genome using the Hidden Markov Model, and their expression patterns were analyzed in MeJA-treated flowers at different developmental stages, revealing structural and expression differences among them [ 34 ]. However, the aforementioned studies were limited to transcriptomic or bioinformatic analyses and did not further validate the functions of the identified HCT genes in C. tinctorius .…”
Section: Discussionmentioning
confidence: 99%
“…Yang, Min et al showed that 31 unigenes encoded 15 key enzymes, mainly related to flavonoid biosynthesis, and HCT was one of them [ 61 ]. Fan S et al found that the CtHCT gene appeared to be associated with abiotic stress response through expression profiling of different flowering stages under light and MeJA treatment [ 62 ]. Jim et al found that PtoHCT9 and PtoHCT10 are active in winter and play a role in plant development and response to cold stress [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAM production was shown to be significantly inhibited by a mutation in the STM ( SHOOTMERISTEMLESS ) [ 3 ]. KNAT7 played a role in secondary cell wall biosynthesis [ 8 , 9 ]. Cotton fiber synthesis is controlled by GhKNL1, a member of the TALE family [ 10 ].…”
Section: Introductionmentioning
confidence: 99%